Descrições em Etnomatemática: descrevendo "a matemática de uma prática" ou "uma prática matematicamente"? - Roger Miarka (Revista Latinoamericana de Etnomatemática, 2013)
This paper aims to discuss the meaning of the description of a practice within Ethnomathematics. For that, we start revealing what a description is by using a discussion by Ostrower (1983) on different perspectives about the relation between a painter and his painting. In sequence, we take into consideration a conception of description that does not separate describer from a described practice. Within this idea, we point out what the Ethnomathematics researcher’s role within this vision would be, as well as a methodological path based on Alangui’s Mutual Interrogation methodology (2006).